Preparation of Fe–Al Binary Thermoelectric Conversion Films by Electrodeposition in AlCl3–NaCl–KCl–FeCl2 Quaternary Molten Salts. Issue 1 (21st January 2021) - Yamamoto, Hiroaki; Koma, Yuki; Kishino, Risa; Nozaki, Ai; Morishita, Masao
Abstract : The electrodeposition of Fe–Al alloy in AlCl3 –NaCl–KCl–FeCl2 quaternary molten salts was investigated by potentiostatic electrolysis to prepare Fe–Al alloy film with a thermoelectric conversion function. In the AlCl3 –NaCl–KCl–FeCl2 molten salts with an AlCl3 /FeCl2 mole ratio of 200 (FeCl2 : 32.6 mmol l −1 ), the electrodeposited Al formed a solid solution with Fe in the potential range from 0.5 to 0.2 V vs Al(III)/Al and formed the intermetallic compound of Fe3 Al at the potential of 0.1 V. Fe–Al alloys containing 0.8–34.5 mol% Al were obtained by controlling the AlCl3 /FeCl2 mole ratio (FeCl2 concentration) in AlCl3 –NaCl–KCl–FeCl2 molten salts and the applied potential in the potential range from 0.2 to −0.1 V vs Al(III)/Al. The Fe–Al alloy films prepared in the present study exhibited the p- or n-type thermoelectric conversion, depending on their composition.